Of Religious Diseases and Sociological Laboratories: Towards a Transnational Anatomy of Catholic Secularisation Narratives in Western Europe, 1940–1970 - Dols, Chris (Journal of religion in Europe, 2016)
This article focuses on various unexplored transnational aspects of Catholic secularisation narratives in the French, Dutch, and West German Church Provinces between 1940 and 1970. It argues that the Dutch Kaski institute, especially, paved the way for transnational entanglement, not only by launching a scientific journal and organising international conferences, but also by establishing an international umbrella institute. With regard to the discursive structure of secularisation narratives, it suggests that an amalgamation of words, figures, and/or cartograms made particular sociological analyses of religiosity so pervasive. An understanding of the historical origins of Catholic secularisation narratives is key to the study of pastoral sociology because these narratives helped legitimise the acting of sociologists in the ecclesiastical domain.